House-infesting Ants (Hymenoptera: Formicidae) in a Municipality of Southeastern Brazil - da Silva, Tiago Felix; Solis, Daniel Russ [UNESP]; Moretti, Thiago de Carvalho; da Silva, Almir Calazans; El Din Mostafa Habib, Mohamed Ezz (California State University, 2009)
In Brazil, since the studies on urban ants started only in the 1980's, the urban myrmecofauna is still poorly known. Therefore, we herein carried out a survey of the myrmecofauna associated with residences in the municipality of Campinas, São Paulo state, Brazil, with the aim of verifying the existing ant species and their dynamics, which may be used in pest management programs. For this survey, baits and manual collection were utilized in the peridomiciles and intradomiciles of 38 houses. 4,308 samples were obtained, 51% of which presented ants, from five subfamilies, 18 genera and 19 species. The predominant subfamily was Myrmicinae, with 8 species. The predominant species was Tapinoma melanocephalum. In the intradomicile, during the diurnal period, the most visited rooms were the kitchen and the living room; during the nocturnal period, the kitchen was the most visited room.
Keywords: Ant Survey; Tramp Species; Myrmicinae; Tapinoma melanocephalum; Camponotus rufipes